2016
DOI: 10.1038/ncomms11001
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of amorphous shear bands at nanotwins in boron suboxide

Abstract: The roles of grain boundaries and twin boundaries in mechanical properties are well understood for metals and alloys. However, for covalent solids, their roles in deformation response to applied stress are not established. Here we characterize the nanotwins in boron suboxide (B6O) with twin boundaries along the planes using both scanning transmission electron microscopy and quantum mechanics. Then, we use quantum mechanics to determine the deformation mechanism for perfect and twinned B6O crystals for both pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
7
37
0
Order By: Relevance
“…A similar structure transformation from the nanotwinned phase to the crystalline phase was also observed in B 6 O. 24 The details of the deformation process for nanotwinned B 12 P 2 under biaxial shear 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 5912 deformation is displayed in Fig. 4(d)-(f).…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 48%
See 1 more Smart Citation
“…A similar structure transformation from the nanotwinned phase to the crystalline phase was also observed in B 6 O. 24 The details of the deformation process for nanotwinned B 12 P 2 under biaxial shear 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 5912 deformation is displayed in Fig. 4(d)-(f).…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 48%
“…Later, we showed that the (B 12 ) icosahedra in B 6 O are deconstructed when it is sheared along (001)/<100> slip system under indentation stress conditions. 24 For B 12 P 2 we first examined the deformation process under indentation stress conditions by applying the biaxial shear deformation along the most plausible slip system (001)/<100>. Then we examined how the nanotwins affect the deformation mechanism by applying both pure shear and biaxial shear deformation along the TB slip system which corresponds to the most plausible slip system in crystalline B 12 P 2 .…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…To examine how nanoscale twins affect the mechanical properties of r‐LiB 13 C 2 , we constructed the nanotwinned r‐LiB 13 C 2 , as shown in Figure C. Here we used the (010) plane as the twin plane since the previous study suggests that the {100} rhombohedral plane is the twin plane for B 4 C, B 6 O, and other related icosahedral materials . The DFT optimized lattice constant for nanotwinned r‐LiB 13 C 2 are a = 5.322 Å, b = 18.255 Å, c = 5.322 Å, and β = 115.79°.…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods will indulge unfavorable effects such as decreasing ductility and developing brittleness . Considering that TBs normally have a lower interfacial energy than normal GBs, it is advisable to incorporate nanoscale twins into metals and ceramics to enhance their strength . For example, ultrastrength phenomena have been observed in nanotwinned InSb and Bi 2 Te 3 due to various strengthening mechanisms such as forming stronger GB bonding in Bi 2 Te 3 and suppressing the easy shear slip in InSb, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, below a critical size, sliding or migration of GBs dominates the deformation mechanism, leading to reduced material strength [16,17]. This grain size effect has been widely examined in metal alloys and ceramics [18][19][20], but not in nanocrystalline semiconductors. TBs are expected to have a much lower formation energy than GBs, making TBs more stable than GBs, which can make them more effective in strengthening materials [21].…”
mentioning
confidence: 99%